Structure-Activity Correlations with Compounds Related to Abscisic Acid - Sondheimer, Ernest (1970)
Inhibition of cell expansion of excised embryonic axes of Phaseolus vulgaris was used to evaluate the growth-inhibiting activity of abscisic acid and related compounds. None of the 13 compounds tested was as active as abscisic acid. 4-Hydroxyisophorone, a substance representative of the abscisic acid ring system was essentially inactive; cis, trans-3-methylsorbic acid, a compound resembling the side chain of abscisic acid, had low activity; and cis, trans-β-ionylideneacetic acid was one-sixth as active. Loss of the ring double bond results in a drastic decrease in biological activity. Comparison of our results with those reported previously leads to the suggestion that the double bond of the cyclohexyl moiety may have an important function in determining the degree of activity of cis, trans-ionylideneacetic acids. Two modes of action are discussed. It seems possible that the ring double bond is involved in covalent bonding in binding of the abscisic acid analogue to macromolecules. This may require formation of an intermediate epoxide. It can also be argued that stereochemical differences between cyclohexane derivatives are important factors in determining the degree of biological activity.